Pelatihan Mikrokontroler Arduino Untuk Siswa-Siswi SMK Negeri 2 Kabupaten Tangerang - Erik Agustian Yulanda; Sari Amalia; Muhammad Syekhurohim (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Based on the idea of fostering creativity among students of SMK Negeri 2 Tangerang Regency so that they can participate in technological developments and be able to create new microcontroller-based technologies that are useful for society, lecturers and students from Electrical Engineering Study Program, Pamulang University carry out Community Service activities (PKM ) at SMK Negeri 2 Tangerang Regency. The implementation of PKM is in the form of Arduino microcontroller training education which includes: basic introduction to electronic and Arduino components, basic introduction to Arduino IDE programming, and how to assemble electronic components with Arduino. Arduino training, which is packaged in a fun and easy-to-understand form, aims to be able to create training activities that meet the elements of knowledge, skills, techniques, attitudes, and ethics for students of SMK Negeri 2 Tangerang Regency in receiving training materials. The results of the PKM activity showed that participants were able to recognize electronic components and Arduino, were able to upload the Arduino IDE program onto the Arduino microcontroller, and were able to represent the new knowledge gained in the form of experiments assembling electronic components using Arduino independently.